Hf-Ta-Si-B-O self-healing antioxidant bionic glass membrane and preparation method thereof
By applying Hf-Ta-Si-B-O composite glass film on the surface of the ceramic matrix, the problem of severe oxidation of boron/silicon-based ceramic coating in high-temperature environments is solved, and the self-healing and anti-oxidation performance of ceramic materials is improved.
Patent Information
- Application Number
- CN202411943633.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The boron/silicon-based ceramic coating is severely oxidized in high-temperature environments, resulting in increased defects such as pores and cracks, poor stability of the glass film and weak repair ability, making it difficult to effectively repair defects in the coating.
The Hf-Ta-Si-B-O composite phase biomimetic glass film was prepared by the method of 'slurry brushing-draining-heat treatment', and through good bonding with the ceramic matrix, a self-healing antioxidant bionic glass film was formed.
It effectively avoids oxidation damage to ceramic materials in high-temperature environments, improves the self-healing and repairing ability and antioxidant properties of the coating, and ensures the high-temperature stability of the glass film.
Smart Images

Figure CN119751120A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-temperature anti-oxidation coatings, and in particular relates to a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film and a preparation method thereof. Background Art
[0002] Silicon-based ceramics such as SiC, MoSi2, etc., and ultra-high temperature borides such as HfB2, ZrB2, TaB2, etc. have excellent properties such as high melting point, stable chemical properties, and high temperature resistance. After oxidation, they can form a layer of low oxygen permeability boron / silicon-based glass film on the surface, so they are widely used as anti-oxidation ceramic coating materials on the surface of carbon structural materials. However, the oxidation rate of boron / silicon-based ceramic coatings is low in low-temperature environments, and the generated amorphous glass film is not uniform and complete enough, making it difficult to effectively repair defects such as holes and cracks in the coatings; boron / silicon-based ceramic coatings are severely oxidized in high-temperature environments above 1500℃, and the coating components are rapidly oxidized and expanded, and a large amount of volatile gases are generated, and the defects such as pores and cracks in the coatings increase significantly, the stability of the glass film is poor, and the repair ability is weakened. Based on the above problems, in order to improve the antioxidant properties of ceramic materials, researchers have designed the structure and oxidation method of ceramic coatings, such as designing porous pre-coatings, pre-oxidation film formation regulation of ceramic coatings, etc., but these methods still have the disadvantages of high porosity in ceramic coating materials, many oxidation active points, and poor self-generated film effect.
[0003] Document 1 "SiC-Si coating with micro-pores to protect carbon / carbon composites against oxidation. Xiaofei Zhu, Yulei Zhang, Yangyang Su, Yanqin Fu, Pei Zhang. Journal of the European Ceramic Society, 2021, 41(1): 114-120." discloses a two-step method for preparing a double-layer SiC-Si ceramic coating with micropores. The method first uses an embedding method to prepare a SiC-Si inner coating, and then uses a slurry method and a heat treatment process to prepare a SiC-Si outer coating containing a microporous structure. The method is easy to operate, the process is simple and easy to control, and oxygen can diffuse into the porous ceramic through the micropores to produce more SiO2 glass to protect the substrate from oxidation. However, the coating prepared by this method has high porosity, low density, and many oxidation active points. It is possible that the silicon-based glass generated by severe oxidation in a high-temperature environment above 1500°C has pores that have not been healed in time, and oxygen will further penetrate into the interior through the pores. In addition, the large amount of volatile gases generated by the oxidation of the coating will escape, which can damage the integrity of the glass film, resulting in more and more defects in the ceramic coating and weakened oxygen barrier ability.
[0004] Document 2 "Effect of flm-forming regulation of the self-formed compound layer on the oxidation inhibition capacity of HfB2-SiC coating. Binbin Wu, Peipei Wang, Xuanru Ren, Mingcheng Zhang, Yuexing Chen, Tengfei Kan, Dalin Shi, Xueqin Kang, Peizhong Feng. Ceramics International, 2022, 48 (15): 22039-22052." discloses a method for preparing an anti-oxidation glass film by pre-oxidation treatment on the surface of a ceramic coating. This method regulates the film formation of the HfB2-SiC ceramic coating at different pre-oxidation temperatures and different pre-oxidation times, and finds that pre-oxidation of the ceramic coating at a suitable temperature and for a suitable time can avoid severe oxidation damage at 1700°C and improve the dynamic stability and oxygen barrier capacity of the coating. However, the pre-oxidation self-generated film is still formed on the basis of damaging the coating itself. In the process of oxidizing the self-generated film, problems such as coating loss, oxidation holes left by the reaction, and uneven distribution of various phases in the glass film will occur. In addition, in the initial stage of pre-oxidation when the film is not fully formed, oxygen can still diffuse into the coating and the substrate through the pores in the coating.
[0005] Avoiding damage to the self-generated film of ceramic materials during oxidation and improving the quality of their film formation are the keys to improving the high-temperature oxidation resistance of boron / silicon-based ceramic materials. Summary of the invention
[0006] The purpose of the present invention is to provide a Hf-Ta-Si-BO self-healing antioxidant bionic glass film and a preparation method. The Hf-Ta-Si-BO composite bionic glass film is prepared by the "slurry brushing-drainage-heat treatment" method, so that the prepared glass film has a good bonding effect with the ceramic matrix, thereby solving the problems of severe oxidation of ceramic materials in high temperature environments, a large increase in defects such as pores, poor self-generated film effects, and weakened antioxidant self-repairing capabilities, thereby providing a simple and effective method for improving the antioxidant properties of boron / silicon-based ceramic materials.
[0007] The technical solution of the present invention is as follows:
[0008] A Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film and a preparation method, the steps are as follows:
[0009] S1. The ZrB2-SiC ceramic substrate is polished and ultrasonically cleaned, placed in an oven for drying, and set aside;
[0010] S2. The borosilicate glass powder, HfO2 powder, Ta2O5 powder were placed in a ball mill and mixed and stirred evenly for standby;
[0011] S3. The mixed powder is heat treated to form a molten multiphase glass, which is then taken out and cooled to room temperature;
[0012] S4. The processed composite glass is placed in a mortar and crushed. After crushing, it is placed in a ball mill for ball milling;
[0013] S5. The ground composite glass powder is placed in the silica sol, magnetically mixed and stirred to prepare a slurry for later use;
[0014] S6. The slurry obtained in S5 is evenly applied to the surface of the ceramic substrate obtained in S1, placed in an oven, drained and dried for standby use, to obtain a sample;
[0015] S7. Place the dried sample in a resistance furnace for heat treatment;
[0016] S8. Place the sample obtained in S7 in an oxidation furnace and heat it up as the furnace forms a film. The temperature is raised at a uniform rate from room temperature to 1600° C. to complete the preparation of the Hf-Ta-Si-BO bionic glass film.
[0017] As an improvement, the mass ratio of the borosilicate glass powder, HfO2 powder and Ta2O5 powder in step S2 is: 7-15: 8-18: 0-2.
[0018] As an improvement, the mixing and stirring time in step S2 is 2.5-3.5 hours.
[0019] As an improvement, the heat treatment temperature in step S3 is 1300° C. and the heat treatment time is 20-40 min.
[0020] As an improvement, the ball milling in step S4 uses a high-energy ball mill, and the ball milling time is 4-5 hours.
[0021] As an improvement, the mass ratio of silica sol to multiphase glass powder in step S5 is 10:23.
[0022] As an improvement, the temperature of the oven in step S6 is 400° C. and the drying time is 2-3 hours.
[0023] As an improvement, the temperature of the resistance furnace heat treatment in step S7 is 1100-1300° C., and the heat treatment time is 2 hours.
[0024] As an improvement, the uniform heating rate in step S8 is 5°C / min.
[0025] The research and development inspiration of the present invention comes from Masson pine. When Masson pine is injured, the wound will quickly flow out rosin to prevent the invasion of pathogens, and the terpenoid compounds in the rosin will undergo specific mutations and participate in the stress response of the plant, prompting the wound to heal as soon as possible, and realizing rapid self-repair. Masson pine rosin is mainly composed of resin acid and terpene hydrocarbons, terpene hydrocarbons are volatile substances, and resin acid is a non-volatile substance. High-temperature volatile borosilicate glass can be used as "terpene hydrocarbons", and refractory HfO2 and Ta2O5 can be used as "resin acids". Hf-Ta-Si-BO anti-oxidation biomimetic glass film imitating the wound self-healing repair mechanism of Masson pine is prepared, and when cracking ("wound") caused by high and low temperature alternating thermal stress occurs, the flowing glass film ("rosin") quickly fills the crack ("wound"), promotes the rapid healing of the crack ("wound"), and prevents the invasion of oxygen ("pathogens") to the coating interior and the matrix.
[0026] The technical advantages of the present invention are:
[0027] 1. The present invention applies a layer of composite glass powder composed of silica sol, borosilicate glass powder, nano HfO2 powder and nano Ta2O5 powder on the surface of the ceramic substrate, and forms a layer of Hf-Ta-Si-BO bionic glass film after "drainage drying-heat treatment-wide temperature range heat treatment". This method can effectively avoid the self-damage of silicon-based ceramics due to oxidation, and the problems of poor self-film formation effect and weak self-healing repair ability due to high-temperature severe oxidation; at the same time, the high-temperature refractory oxide is evenly dispersed in the glass film, ensuring the high-temperature stability of the glass film, and effectively improving the anti-oxidation performance of silicon-based ceramics.
[0028] 2. The preparation method disclosed in the present invention is simple to operate and saves costs, and the prepared Hf-Ta-Si-BO bionic glass film has good bonding with the ceramic matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a preparation process flow chart of the present invention.
[0030] Figure 2 This is a macroscopic photograph of the composite glass powder applied to the surface of the ceramic substrate after drying in the implementation case of the present invention.
[0031] Figure 3 This is a backscattered electron microscope photograph of the surface of the Hf-Ta-Si-BO bionic glass film prepared in the implementation case of the present invention.
[0032] Figure 4 This is the weight change curve of four samples prepared in the implementation case of the present invention when oxidized at 1700°C. DETAILED DESCRIPTION
[0033] The present invention is described in detail and specifically by specific examples below to provide a better understanding of the present invention, but the following examples do not limit the protection scope of the present invention.
[0034] Example 1
[0035] This embodiment discloses a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film and a preparation method, the steps are as follows:
[0036] S1. After grinding and polishing, the ZrB2-SiC ceramic substrate is ultrasonically cleaned and placed in an oven for drying.
[0037] S2. Place borosilicate glass powder, HfO2 powder and Ta2O5 powder in a ball mill in a mass ratio of 10:13:0 and mix for 3 hours until evenly stirred for later use.
[0038] S3. The mixed powder is heat treated at 1300°C for 30 minutes to form a molten multiphase glass, which is then taken out and cooled to room temperature.
[0039] S4. Place the processed composite glass in a mortar and crush it with a pestle. After crushing, place it in a high-energy ball mill and grind it for 5 hours for later use.
[0040] S5. Put the ground multiphase glass powder into silica sol with a mass ratio of silica sol to multiphase glass powder of 10:23, mix and stir magnetically for 2 hours to prepare a slurry for later use.
[0041] S6. The slurry obtained in S5 is evenly applied to the surface of the ceramic substrate obtained in S1, and placed in an oven at a temperature of 400°C for 2 hours, and then drained and dried for later use. This sample is recorded as HT0, and its macroscopic morphology after application and drying is as follows: Figure 2 shown.
[0042] S7. Place the dried HT0 sample in a resistance furnace for heat treatment at 1300℃ for 2 hours for later use.
[0043] S8. Place the sample obtained in S7 in an oxidation furnace and heat it up to form a film. The heating rate is 5°C / min. The temperature is raised from room temperature to 1600°C. The Hf-Ta-Si-BO bionic glass film is ready for use. The surface microstructure of the prepared bionic glass film is as follows: Figure 3 (a) shown.
[0044] S9. Weigh the sample coated with Hf-Ta-Si-BO biomimetic glass film in S8 on an analytical balance and record the weight. Then, place it in an oxidation furnace heated to 1700°C for oxidation test. Take out the sample and weigh it every 10 minutes. Calculate the cumulative weight change as follows: Figure 4 shown.
[0045] After the above steps, the HT0 sample was oxidized at 1700℃ for 100 minutes, and the weight gain was 1.138×10 -2 g / cm 2 .
[0046] Embodiment 2:
[0047] This embodiment discloses a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film and a preparation method, the steps are as follows:
[0048] S1. After grinding and polishing, the ZrB2-SiC ceramic substrate is ultrasonically cleaned and placed in an oven for drying.
[0049] S2. Place borosilicate glass powder, HfO2 powder and Ta2O5 powder in a ball mill in a mass ratio of 15:18:1 and mix them for 3 hours until they are evenly stirred and set aside.
[0050] S3. The mixed powder is heat treated at 1300°C for 30 minutes to form a molten multiphase glass, which is then taken out and cooled to room temperature.
[0051] S4. Place the processed composite glass in a mortar and crush it with a pestle. After crushing, place it in a high-energy ball mill and grind it for 5 hours for later use.
[0052] S5. Put the ground multiphase glass powder into silica sol with a mass ratio of silica sol to multiphase glass powder of 10:23, mix and stir magnetically for 2 hours to prepare a slurry for later use.
[0053] S6. The slurry obtained in S5 is evenly applied to the surface of the ceramic substrate obtained in S1, and placed in an oven at a temperature of 400°C for 2 hours, and then drained and dried for later use. This sample is recorded as HT5, and its macroscopic morphology after application and drying is as follows: Figure 2 shown.
[0054] S7. Place the dried HT0 sample in a resistance furnace for heat treatment at 1300℃ for 2 hours for later use.
[0055] S8. Place the sample obtained in S7 in an oxidation furnace and heat it up to form a film. The heating rate is 5°C / min. The temperature is raised from room temperature to 1600°C. The Hf-Ta-Si-BO bionic glass film is ready for use. The surface microstructure of the prepared bionic glass film is as follows: Figure 3 (b) as shown.
[0056] S9. Weigh the sample coated with Hf-Ta-Si-BO biomimetic glass film in S8 on an analytical balance and record the weight. Then, place it in an oxidation furnace heated to 1700°C for oxidation test. Take out the sample and weigh it every 10 minutes. Calculate the cumulative weight change as follows: Figure 4 shown.
[0057] After the above steps, the HT5 sample was oxidized at 1700℃ for 100 minutes, and the weight gain was 1.023×10 -2 g / cm 2 .
[0058] Embodiment 3:
[0059] This embodiment discloses a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film and a preparation method, the steps are as follows:
[0060] S1. After grinding and polishing, the ZrB2-SiC ceramic substrate is ultrasonically cleaned and placed in an oven for drying.
[0061] S2. Place borosilicate glass powder, HfO2 powder and Ta2O5 powder in a ball mill in a mass ratio of 7:8:1 and mix them for 3 hours until they are evenly stirred and set aside.
[0062] S3. The mixed powder is heat treated at 1300°C for 30 minutes to form a molten multiphase glass, which is then taken out and cooled to room temperature.
[0063] S4. Place the processed composite glass in a mortar and crush it with a pestle. After crushing, place it in a high-energy ball mill and grind it for 5 hours for later use.
[0064] S5. Put the ground multiphase glass powder into silica sol with a mass ratio of silica sol to multiphase glass powder of 10:23, mix and stir magnetically for 2 hours to prepare a slurry for later use.
[0065] S6. The slurry obtained in S5 is evenly applied to the surface of the ceramic substrate obtained in S1, and placed in an oven at a temperature of 400°C for 2 hours, and then drained and dried for later use. This sample is recorded as HT10, and its macroscopic morphology after application and drying is as follows: Figure 2 shown.
[0066] S7. Place the dried HT0 sample in a resistance furnace for heat treatment at 1300℃ for 2 hours for later use.
[0067] S8. Place the sample obtained in S7 in an oxidation furnace and heat it up to form a film. The heating rate is 5°C / min. The temperature is raised from room temperature to 1600°C. The Hf-Ta-Si-BO bionic glass film is ready for use. The surface microstructure of the prepared bionic glass film is as follows: Figure 3 As shown in (c), with the increase of Ta2O5 content in the bionic glass film, the uniform dispersion of refractory oxides in the glass film improves.
[0068] S9. Weigh the sample coated with Hf-Ta-Si-BO biomimetic glass film in S8 on an analytical balance and record the weight. Then, place it in an oxidation furnace heated to 1700°C for oxidation test. Take out the sample and weigh it every 10 minutes. Calculate the cumulative weight change as follows: Figure 4 shown.
[0069] After the above steps, the HT10 sample was oxidized at 1700℃ for 100 minutes, and the weight gain was only 0.721×10 -2 g / cm 2 , which were reduced by 36.6%, 29.5% and 27.0% compared with HT0, HT5 and HT15 samples respectively. The HT10 sample had the smallest weight change at 1700℃ and the best anti-oxidation effect. The proper addition of Ta2O5 and its interaction with HfO2 and SiO2 made the HT10 sample glass film have the best self-healing repair ability.
[0070] Embodiment 4:
[0071] This embodiment discloses a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film and a preparation method, the steps are as follows:
[0072] S1. After grinding and polishing, the ZrB2-SiC ceramic substrate is ultrasonically cleaned and placed in an oven for drying.
[0073] S2. Place borosilicate glass powder, HfO2 powder and Ta2O5 powder in a ball mill in a mass ratio of 10:11:2 and mix for 3 hours until evenly stirred for later use.
[0074] S3. The mixed powder is heat treated at 1300°C for 30 minutes to form a molten multiphase glass, which is then taken out and cooled to room temperature.
[0075] S4. Place the processed composite glass in a mortar and crush it with a pestle. After crushing, place it in a high-energy ball mill and grind it for 5 hours for later use.
[0076] S5. Put the ground multiphase glass powder into silica sol with a mass ratio of silica sol to multiphase glass powder of 10:23, mix and stir magnetically for 2 hours to prepare a slurry for later use.
[0077] S6. The slurry obtained in S5 is evenly applied to the surface of the ceramic substrate obtained in S1, and placed in an oven at a temperature of 400°C for 2 hours, and then drained and dried for later use. This sample is recorded as HT15. Its macroscopic morphology after application and drying is as follows: Figure 2 shown.
[0078] S7. Place the dried HT0 sample in a resistance furnace for heat treatment at 1300℃ for 2 hours for later use.
[0079] S8. Place the sample obtained in S7 in an oxidation furnace and heat it up to form a film. The heating rate is 5°C / min. The temperature is raised from room temperature to 1600°C. The Hf-Ta-Si-BO bionic glass film is ready for use. The surface microstructure of the prepared bionic glass film is as follows: Figure 3 (d) as shown.
[0080] S9. Weigh the sample coated with Hf-Ta-Si-BO biomimetic glass film in S8 on an analytical balance and record the weight. Then, place it in an oxidation furnace heated to 1700°C for oxidation test. Take out the sample and weigh it every 10 minutes. Calculate the cumulative weight change as follows: Figure 4 shown.
[0081] After the above steps, the HT15 sample was oxidized at 1700℃ for 100 minutes, and the weight gain was 0.990×10 -2 g / cm 2 The strong complexation of excess Ta2O5 in the glass film weakens the self-healing repair ability of the glass film, and its antioxidant performance is reduced compared with that of the HT10 sample.
[0082] The water content of the silica sol in all the above embodiments is 70%; the purity of the HfO2 powder and Ta2O5 powder is
[0083] >99.95%, particle size is 1000 mesh.
[0084] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not equivalent to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.
Claims
1. A method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film, characterized in that: Here are the steps: S1. The ZrB2-SiC ceramic substrate is polished and ultrasonically cleaned, placed in an oven for drying, and set aside; S2. The borosilicate glass powder, HfO2 powder, Ta2O5 powder were placed in a ball mill and mixed and stirred evenly for standby; S3. The mixed powder is heat treated to form a molten multiphase glass, which is then taken out and cooled to room temperature; S4. The processed composite glass is placed in a mortar and crushed. After crushing, it is placed in a ball mill for ball milling; S5. The ground composite glass powder is placed in the silica sol, magnetically mixed and stirred to prepare a slurry for later use; S6. The slurry obtained in S5 is evenly applied to the surface of the ceramic substrate obtained in S1, placed in an oven, drained and dried for standby use, to obtain a sample; S7. Place the dried sample in a resistance furnace for heat treatment; S8. Place the sample obtained in S7 in an oxidation furnace and heat it up as the furnace forms a film. The temperature is raised at a uniform rate from room temperature to 1600° C. to complete the preparation of the Hf-Ta-Si-BO bionic glass film.
2. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation biomimetic glass film according to claim 1, characterized in that: The mass ratio of the borosilicate glass powder, HfO2 powder and Ta2O5 powder in step S2 is: 7-15: 8-18: 0-2.
3. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film according to claim 1, characterized in that: The mixing and stirring time in step S2 is 2.5-3.5 hours.
4. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation biomimetic glass film according to claim 1, characterized in that: The heat treatment temperature in step S3 is 1300° C., and the heat treatment time is 20-40 min.
5. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film according to claim 1, characterized in that: The ball milling in step S4 uses a high-energy ball mill, and the ball milling time is 4-5 hours.
6. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation biomimetic glass film according to claim 1, characterized in that: In step S5, the mass ratio of silica sol to multiphase glass powder is 10:
23.
7. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film according to claim 1, characterized in that: In step S6, the temperature of the oven is 400° C. and the drying time is 2-3 hours.
8. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film according to claim 1, characterized in that: The temperature of the resistance furnace heat treatment in step S7 is 1100-1300° C., and the heat treatment time is 2 hours.
9. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film according to claim 1, characterized in that: The uniform heating rate in step S8 is 5°C / min.
10. The method for preparing a Hf-Ta-Si-BO self-healing anti-oxidation bionic glass film according to claim 1, characterized in that: The water content of the silica sol in step S5 is 70%; the purity of the HfO2 powder and Ta2O5 powder is >99.95%, and the particle size is 1000 mesh.
Citation Information
Patent Citations
Function-transferring object, method for transferring functional layer, package and function-transferring film roll
CN104749879A
Molybdenum-based composite coating and preparation method thereof
CN106853436A
Coatings having controlled roughness and microstructure
CN111132945A
Hf-Ta-Si / (Hf, Zr) B2 layered composite ultrahigh-temperature protective coating and preparation method thereof
CN117702105A
Porous silica glass membrane and its production
JP1999267479A
Cited By
Carbon fiber reinforced silicon carbide-based composite material with anti-ablation gradient composite coating on surface and preparation method of carbon fiber reinforced silicon carbide-based composite material
CN121248305A